Optimizing Civil Servant Performance Management through Internal Compliance Distance Learning Program - Victorianus Mario Isdianto Bimo Adi; Nabila Syafira; C. Cedaryana (Manunggal Halim Jaya, 2026)
While in public sector organizations, internal compliance is regarded as one of the main human resource control mechanisms in supporting the implementation of effective public sector performance management, it is suspected that there is weak empirical evidence of whether or not distance learning as a scaled-up technique for building competency is effective in producing behavioral change among the Civil Servants (ASN), let alone effective in its ability to produce performance outcomes. The purpose of this study is to conduct an evaluation of the Distance Learning Program (PJJ) implementation and effectiveness in terms of skill change at the level of behaviors after training at these Directorate General of Customs and Excise. The study used a quantitative method that used a 360-degree questionnaire and asked 29 alumni, their supervisors and colleagues to complete the questionnaire at a level 3 (behavioral) post-training evaluation approach, instrument validity was confirmed by Cronbach's Alpha testing, competitor change was found by comparing the pre-test and post-test results. The results indicate that average competency score of respondents before undergoing the training ranged from 7.43–8.22 and after training ranged from 9.17–9.49 in various sub-activities, while respondents also supported that the training was able to transfer knowledge and change their behavior in the workplace. These findings theoretically contribute to the limited literature on the relationship between the outcomes of distance learning and the performance management of civil servants' compliance efforts in the public sector and provide policymakers evidence on how to continue developing and scaling distance-based training in the scope of integrated civil servant competency development strategies.